A systems serology approach to the investigation of infection-induced antibody responses and protection in trachoma - Barton, Amber; Rosenkrands, Ida; Pickering, Harry; Faal, Nkoyo; Harte, Anna; Joof, Hassan; Makalo, Pateh; Ragonnet, Manon; Olsen, Anja Weinreich; Bailey, Robin L.; Mabey, David C. W.; Follmann, Frank; et al. (Frontiers in Immunology, 2023)
Background: Ocular infections with Chlamydia trachomatis serovars A-C cause the neglected tropical disease trachoma. As infection does not confer complete immunity, repeated infections are common, leading to long term sequelae such as scarring and blindness. Here we apply a systems serology approach to investigate whether systemic antibody features are associated with susceptibility to infection. Methods: Sera from children in five trachoma endemic villages in The Gambia were assayed for 23 antibody features: IgG responses towards two Chlamydia trachomatis antigens and three serovars (elementary bodies and major outer membrane protein MOMP, serovars A-C), IgG responses towards five MOMP peptides (serovars A-C), neutralization and antibody-dependent phagocytosis. Participants were considered resistant if they subsequently developed infection only when over 70% of other children in the same compound were infected. Results: The antibody features assayed were not associated with resistance to infection (false discovery rate < 0.05). Anti-MOMP SvA IgG and neutralization titer were higher in susceptible individuals (p < 0.05 before multiple testing adjustment). Classification using partial least squares performed only slightly better than chance in distinguishing between susceptible and resistant participants based on systemic antibody profile (specificity 71%, sensitivity 36%). Conclusions: Systemic infection-induced IgG and functional antibody responses do not appear to be protective against subsequent infection. Ocular responses, IgA, avidity or cell-mediated responses may play a greater role in protective immunity than systemic IgG.